Primary Membranous Nephropathy Flare After COVID-19 Vaccination - Kelly, V. Liang; Syeda, B. Ahmad; Elizabeth, C. Kurtz; Matthew, Pittappilly; Marta, I. Minervini (Journal of Nephrology Advances, 2024)
Primary membranous nephropathy (MN) is due to autoantibodies to phospholipase A2 receptor (PLA2R Ab). It is unclear whether COVID-19 vaccines can trigger flares of glomerular diseases such as primary MN. There have been increasing reports of glomerular diseases presenting or flaring after receipt of COVID-19 vaccines. We present a patient with primary MN who developed nephrotic syndrome after receiving her second mRNA-1273 COVID-19 vaccine with positive PLA2R Ab. Renal biopsy confirmed primary MN. She was treated for her primary MN flare with rituximab in a manner similar to non-vaccine-associated MN, which led to significant reduction in both PLA2R Ab level and proteinuria. This case adds to the growing literature on MN flares after receipt of mRNA COVID-19 vaccines. Close follow-up of patients with primary MN and other glomerular diseases after COVID-19 vaccination is warranted. Further research is needed to determine the pathophysiology behind vaccine-induced MN flares and whether there is a potential association between exposure to SARS-CoV-2 antigens and loss of tolerance to the PLA2R antigen.
Keywords: Membranous nephropathy; COVID-19; vaccines; flares; glomerular diseases; PLA2R